Control flow versus communication: comparing two approaches to process modelling. Issue 2 (10th February 2022) - Moattar, Haleh; Bandara, Wasana; Kannengiesser, Udo; Rosemann, Michael
Abstract : Purpose: Business process modelling integrates and visualizes relevant information essential for managing day-to-day business operations. It plays a critical role in the design and execution of business transformations. Recognizing the role of process modelling, a large number of modelling languages, methods and techniques have been developed, each offering diverse advantages and having inherent limitations. Traditional and popular process modelling approaches focus on the exact specification of the control flow of business processes, whereas more recent approaches like Subject-oriented Business Process Management (S-BPM) are focused on the communication between process participants. This study aims to provide comparative insights about these two approaches through their experimental application. This study does so by comparing Business Process Model and Notation (BPMN); a control flow approach, with S-BPM; a communication approach, with a specific focus on their suitability for novice modellers. Design/methodology/approach: This paper reports on an exploratory experiment that compares BPMN to S-BPM. Applying cognitive load theory, this study compares the experiences and outcomes of novice process modellers, assessing perceived ease of use, model quality (syntactic and semantic) and modelling efficiency (time to model) across the two approaches. Findings: Study results show that S-BPM (a communication approach) led to significantly better user performances for process modelling than BPMN (a control flow approach). This study points to how a different modelling approach such as S-BPM could be either considered as an alternative or to complement the more popular control flow approach BPMN. This observation was especially relevant for modelling contexts where domain experts are novice process modellers. Originality/value: This study provides the first empirical evidence that communication approaches like S-BPM could outperform modelling approaches which are control-flow based (i.e. BPMN), especially when being used by novice process modellers who hold the domain and process knowledge. This study uses this as a springboard to present important considerations for practice and guide future process modelling research.